Transparency and Accountability in Local Public Finance: Evidence from Public Parking Fee Allocation - Misheva, Kristina; Panev, Kristijan (Review of European and Comparative Law, 2025)
Municipalities worldwide play a crucial role in delivering essential public services to citizens. However, securing adequate resources and sustainable funding remains a persistent challenge for local self-governments. Depending on the state system, local circumstances, societal needs, and policy priorities, municipal revenue structures vary significantly. Yet modern urban municipalities are generally guided by common principles such as equality, solidarity, efficiency, transparency, accountability, and the promotion of public well-being. The adoption of the European Charter of Local Self-Government in the 1980s established an internationally recognized legal framework for local governance and local financing. As a member state of the Council of Europe, North Macedonia adheres to the Charter’s core principles, which emphasize greater local fiscal autonomy and the responsibility of municipalities to manage both their revenues and expenditures independently of the central government. Despite the existing framework, Macedonian municipalities still rely heavily on central government transfers, with own-source revenues – such as property taxes, communal fees, and parking fees – making up a smaller share. Parking fees generally provide modest revenue, mainly funding public-space maintenance, traffic management, and minor infrastructure, and rarely support social welfare. Recently, some cities have introduced structured or solidarity-based parking fees for humanitarian or health purposes. This paper examines the core principles of local financing through an analysis of parking fees, focusing on the emerging practice of “humanitarian parking” as a case study. It employs a qualitative comparative case-study methodology that examines legal frameworks, policies, and practices of public ad solidarity-based parking fees in cities in Macedonia and Serbia, as neighboring countries that share a similar socio-demographic, economic, and legal context. Particular attention is given to the emerging model of “humanitarian parking” as a municipal policy instrument. The analysis assesses the impact of this model on local fiscal autonomy and examines empirical evidence on citizen attitudes, including levels of public support and the transparency of parking-revenue allocation.